Epitaxial growth of an antireflective, conductive, graded index ITO nanowire layer - O'Dwyer, Colm; Sotomayor Torres, Clivia (Frontiers in Physics, 2013)
Nanoporous and nanostructured films, assemblies and arrangements are important from an applied point of view in microelectronics, photonics and optical materials. The ability to minimize reflection, control light output and use contrast and variation of the refractive index to modify photonic characteristics can provide routes to enhanced photonic crystal devices, omnidirectional reflectors, antireflection coatings and broadband absorbing materials. This work shows how multiscale branching of defect-free ITO NWs grown as a layer with a graded refractive index improves antireflection properties and shifts the transparency window into the near-infrared (NIR). The measurements confirm the structural quality and growth mechanism of the NW layer without any heterogeneous seeding for NW growth. Optical reflectance measurements confirm broadband antireflection down to <5% between 1.3-1.6 um which is tunable with the NW density. The work also outlines how the suppression of the Burstein-Moss shifts using refractive index variation allows transparency in a conductive NW layer into NIR range.